Enhancing Primary School Teachers’ Competence through Training on the Implementation of Deep Learning in Barru Regency - Musfirah, Musfirah; Kamaruddin, Kamaruddin; Syawaluddin, Ahmad; Zainal, Zaid; Burhan, Imron (Help: Journal of Community Service, 2025)
This community engagement initiative was designed to support the professional growth of primary school teachers through a focused training on implementing deep learning strategies. The training was held at the Barru District Education Office on July 21–22, 2025, and was a collaborative effort between the office and lecturers from Universitas Negeri Makassar. Primary school teachers from across the Barru Regency participated actively in the program. The training covered three essential topics: (1) Growth Mindset in Deep Learning, (2) the Deep Learning Framework, and (3) Principles and Learning Experiences in Deep Learning. The program was carried out in three main stages: preparation, implementation, and reflection. During the preparation phase, materials, logistics, and technical tools were organized. Over two days of implementation, participants engaged in interactive discussions, collaborative sessions, and practical exercises. In the reflection phase, teachers developed follow-up plans tailored to the needs and context of their respective schools. The program helped deepen teachers’ understanding of deep learning approaches and encouraged more student-centered, reflective classroom practices. It is hoped that this training will contribute to long-term improvements in teaching quality and student engagement in Barru’s primary schools.